2011
DOI: 10.2139/ssrn.1871723
|View full text |Cite
|
Sign up to set email alerts
|

Inequality Aversion and Voting on Redistribution

Abstract: Some people have a concern for a fair distribution of incomes while others do not. Does such a concern matter for majority voting on redistribution? Fairness preferences are relevant for redistribution outcomes only if fair-minded voters are pivotal. Pivotality, in turn, depends on the structure of income classes. We experimentally study voting on redistribution between two income classes and show that the effect of inequality aversion is asymmetric. Inequality aversion is more likely to matter if the "rich" a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…This difference in the cost of sociotropic voting may explain why we observe, in both absolute and relative terms, more sociotropic than inequalityaverse voting (remember that we observed 13 (10.2%) G-subjects demonstrating inequality-averse voting, but 54 (28.1%) L-subjects voting in line with efficiency preferences; see Tables 4 and 6, first votes). Such differences may also explain why some studies find social-welfare preferences to be quantitatively more important than difference aversion (e.g, Ackert et al, 2004;Messer et al, 2010;Engelmann and Strobel, 2004), whereas others find the reverse (e.g., Bolton and Ockenfels, 2006;Sauermann and Kaiser, 2010;Höchtl et al, 2012). In F&R's thought experiment as well as in our empirical experiment, losses were distributed evenly among reform losers, while gains were evenly distributed among reform gainers.…”
Section: ) and Risk Attitudes (Seementioning
confidence: 59%
See 1 more Smart Citation
“…This difference in the cost of sociotropic voting may explain why we observe, in both absolute and relative terms, more sociotropic than inequalityaverse voting (remember that we observed 13 (10.2%) G-subjects demonstrating inequality-averse voting, but 54 (28.1%) L-subjects voting in line with efficiency preferences; see Tables 4 and 6, first votes). Such differences may also explain why some studies find social-welfare preferences to be quantitatively more important than difference aversion (e.g, Ackert et al, 2004;Messer et al, 2010;Engelmann and Strobel, 2004), whereas others find the reverse (e.g., Bolton and Ockenfels, 2006;Sauermann and Kaiser, 2010;Höchtl et al, 2012). In F&R's thought experiment as well as in our empirical experiment, losses were distributed evenly among reform losers, while gains were evenly distributed among reform gainers.…”
Section: ) and Risk Attitudes (Seementioning
confidence: 59%
“…So far, the literature provides an inconclusive picture of whether one motive outweighs the other. Höchtl et al (2012) observed no evidence for voters to be efficiency-loving and showed that inequality averse voters may not matter for redistribution outcomes for empirically plausible cases. Bolton and Ockenfels (2006) investigated the tradeoff between equity and efficiency motives in a voting game with three voters.…”
mentioning
confidence: 94%
“…Tyran and Sausgruber (2006) offer evidence that inequality averse social preferences may explain voting behavior over non-distortionary redistribution, in an experiment where subjects were endowed with one of two different income levels (there is no labor market) and vote on a fixed amount of redistribution. Hochtl et al (2012) report a followup experiment and provide evidence that the ability of inequality aversion to explain voting behavior on redistribution may depend on the pre-tax distribution of income. In all the papers described above, the amount of resources to be distributed is fixed exogenously and participants can only decide how to reallocate this surplus.…”
Section: Related Literaturementioning
confidence: 99%
“…In particular, we contribute to the literature that investigates how non-standard preferences shape voting outcomes (e.g. Höchtl et al 2012, Feddersen et al 2003 and market outcomes (e.g. Fehr and Falk 1999).…”
mentioning
confidence: 99%
“…This argument may matter for aggregate voting outcome because the standard model predicts a close defeat of the discriminatory tax. Under these conditions, a few fairness-minded voters from market 2 suffice to tip the balance (see Tyran andSausgruber 2005 andHöchtl et al 2012). …”
mentioning
confidence: 99%